2022
DOI: 10.3233/cbm-210426
|View full text |Cite
|
Sign up to set email alerts
|

Association of FBXW11 levels with tumor development and prognosis in chondrosarcoma

Abstract: INTRODUCTION: The E3 ubiquitin ligase FBXW11 exerts an oncogenic or tumor suppressive function in a cellular context-dependent manner. However, the clinical significance and biological role of FBXW11 in chondrosarcoma have not been clearly characterized. This study focuses on the expression profile, prognostic value and biological function of FBXW11 in chondrosarcoma. METHODS: FBXW11 expression was analyzed by qRT-PCR and Western blot in six cases of chondrosarcoma specimens and the matched adjacent non-tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Cao et al disclosed that the UPP contributes to receptor-interacting serine/threonine kinase 1 (RIPK1) degradation mediated by optineurin (OPTN) in microglial cells to inhibit the proinflammatory pathways of NF-κB and, thus, suppresses neuroinflammation [ 138 ]. F-box and WD-40-domain protein 11 (FBXW11) is a component of the SCF (Skp1-Cul1-F-box) E3 ubiquitin ligase complex [ 139 , 140 ]. A study conducted by Sun et al showed FBXW11, a component of the SCF E3 ubiquitin ligase complex, was overexpressed in Aβ-stimulated microglia cells and the hippocampus of AD mice, and it enabled the activation of the ASK1/MAPKs/NF-κB inflammatory signaling pathway, thereby contributing to inflammation-induced AD pathology.…”
Section: Epigenetic Regulation In Inflammationmentioning
confidence: 99%
“…Cao et al disclosed that the UPP contributes to receptor-interacting serine/threonine kinase 1 (RIPK1) degradation mediated by optineurin (OPTN) in microglial cells to inhibit the proinflammatory pathways of NF-κB and, thus, suppresses neuroinflammation [ 138 ]. F-box and WD-40-domain protein 11 (FBXW11) is a component of the SCF (Skp1-Cul1-F-box) E3 ubiquitin ligase complex [ 139 , 140 ]. A study conducted by Sun et al showed FBXW11, a component of the SCF E3 ubiquitin ligase complex, was overexpressed in Aβ-stimulated microglia cells and the hippocampus of AD mice, and it enabled the activation of the ASK1/MAPKs/NF-κB inflammatory signaling pathway, thereby contributing to inflammation-induced AD pathology.…”
Section: Epigenetic Regulation In Inflammationmentioning
confidence: 99%
“…A high level of expression of β-TrCP2 has been reported in human cancer cell lines and primary breast tumors [104]. On the contrary, the downregulation of β-TrCP2 has been reported in clinical chondrosarcoma samples [105]. In addition, the recovery of β-TrCP2 suppresses chondrosarcoma cell growth and induces apoptosis.…”
Section: Association Of β-Trcp With Cancermentioning
confidence: 99%